Sob o ataque do agronegócio: relação entre o discurso da Frente Parlamentar Agropecuária e a nulificação da política pública de reforma agrária - Pacheco, Cássia Morgana Faxina (2019)
This academic work aims at a reflection on the analysis of the contemporary performance of the Frente Parlamentar Agropecuária (FPA), its performance within the Brazilian State and its consequences for the progress of public policies, specifically in this work, the public policy of agrarian reform. For this, a historical rescue of the agrarian and agricultural public policies in Brazil is promoted, the unfolding of this conjuncture is reviewed until the separation in distinct State actions according to the publics of each segment and a debate about the origins and the reason for being placed as antagonistic. From bibliographic and documentary research (using the technique of Discourse Analysis), the discourse of the Frente Parlamentar Agropecuária is interpreted in order to identify its roots and consequences for the public policy of agrarian reform for current days. The ideological clash of the Frente Parlamentar Agropecuária in relation to the public policy of agrarian reform can be perceived by language. Discourse analysis can bring to light the FPA’s ideological political stance towards agrarian-oriented public policies. As a result, there is a reactive role in the dispute for the public fund, for territory, for the control of the public policy of agrarian reform and for the relaxation of environmental issues. It is concluded that the debate goes beyond the issues of different agriculture, which no longer turns to the agricultural model which would be most ideal for Brazil, but how an organized group within the state shapes the ideal public policies for its commercial needs.